Povoações, freguesias e vilas na Paraíba Colonial: Pombal e Sousa, 1697-1800 - Sarmento, Christiane Finizola (2007)
The towns presently named Pombal and Sousa, located in the hinterland of the State of Paraíba, Brazil, still keep vestiges of the colonization process they went through along the 18th and 19th centuries, when they both emerged as settlement nuclei in the extreme West of the then captaincy of Paraíba and attained the status of freguesia and vila in a later period. This research aims to comprehend the process of urban formation and development of the colonial urban nuclei of Pombal and Sousa as they became povoados (hamlets), freguesias (parishes) and vilas (small urban communities with a local government), according to territorial expansion policies implemented by the Portuguese government from 1697 to 1800. The choice of the two urban settlements for this survey lies in the fact that they were part of the great conquest and colonization program undertaken by the Portuguese Crown. Another aspect that was considered was the fact that those towns are the oldest urban nuclei of Paraíba s hinterland. They came into being as early as in the times of the colony, thus producing a favorable environment to the study of the changes that occurred in the captaincy s hinterland scenery resulting from the process of formation and development of the colonial urban space. Three fundamental categories of analysis were defined since they have a direct bearing upon the urban configuration of the two colonization nuclei: povoado, freguesia and vila. The three of them are related to civil and ecclesiastic jurisdictions. Field, documentation and bibliography surveys were undertaken in order to develop the study. They allowed for the finding of vestiges of the old, colonial urban structures and for the development of theoretical analysis based on present-day studies of issues relating to the colonial urban history. The study purposes were, therefore, to try to understand how the old urban nuclei of Pombal and Sousa fit in the territorial expansion policies undertaken by the Portuguese government; to relate the process of urban formation and development of such nuclei with the categories of analysis povoação-freguesia-vila by discussing the relations and influences they exert over one another and their territory, as well as to unveil, as much as possible, the configuration the urban spaces that were shaped along the 18th century